2022
DOI: 10.1210/clinem/dgac292
|View full text |Cite
|
Sign up to set email alerts
|

Serum Thrombospondin-2 Levels Are Closely Associated With the Severity of Metabolic Syndrome and Metabolic Associated Fatty Liver Disease

Abstract: Context Metabolic associated fatty liver disease (MAFLD) is the hepatic manifestation of obesity-related metabolic syndrome (MetS). Non-invasive biomarkers for monitoring the progression and severity of these metabolic comorbidities are needed. Objectives To investigate the associations of serum thrombospondin-2 (TSP2) with MetS and MAFLD severity, and the potential diagnostic value of serum TSP2 for identifying at-risk metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…7 In morbidly obese individuals, serum TSP2 levels significantly increased with worsening glucose tolerance and the presence of more components of metabolic syndrome. 8 In T2D patients, higher TSP2 levels were significantly associated with higher BMI, WC, HbA1c, as well as higher CAP and LS measurements on VCTE. 1 In this study, we demonstrated a modest but significant reduction in serum TSP2 levels from baseline in patients treated with dapagliflozin who also experienced HbA1c reduction, weight loss and improvements in hepatic steatosis and fibrosis.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…7 In morbidly obese individuals, serum TSP2 levels significantly increased with worsening glucose tolerance and the presence of more components of metabolic syndrome. 8 In T2D patients, higher TSP2 levels were significantly associated with higher BMI, WC, HbA1c, as well as higher CAP and LS measurements on VCTE. 1 In this study, we demonstrated a modest but significant reduction in serum TSP2 levels from baseline in patients treated with dapagliflozin who also experienced HbA1c reduction, weight loss and improvements in hepatic steatosis and fibrosis.…”
Section: Discussionmentioning
confidence: 81%
“…[5][6][7] Circulating TSP2 was recently identified as a potential novel biomarker of hepatic fibrosis. 1,[8][9][10] In morbidly obese individuals, higher circulating TSP2 levels were associated with increasing severity of hepatic steatosis, inflammation and fibrosis. 1,8 In T2D patients with coexisting NAFLD, baseline circulating TSP2 level was associated with the presence and the development of advanced hepatic fibrosis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…15,16 These results were supported by a large investigation of NAFLD patients with diabetes mellitus or metabolic-associated fatty liver disease. 17,18 Furthermore, a correlation between the degree of fibrosis and inflammation and serum TSP2 levels was observed not only in NAFLD, but also in hepatitis C virus-infected patients. 19,20 Despite these advances, however, the specific liver cell populations responsible for THBS2/TSP2 expression in NAFLD, the underlying mechanisms governing expression dynamics, and the precise role of THBS2/TSP2 in the pathogenesis of NAFLD remain largely unknown.…”
Section: Introductionmentioning
confidence: 89%